2012
DOI: 10.1302/0301-620x.94b4.28023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arthroscopy of the hip for femoroacetabular impingement on quality of life at a mean follow-up of 3.2 years

Abstract: The benefit of arthroscopy of the hip in the treatment of femoroacetabular impingement (FAI) in terms of quality of life (QoL) has not been reported. We prospectively collected data on 612 patients (257 women (42%) and 355 men (58%)) with a mean age at the time of surgery of 36.7 years (14 to 75) who underwent arthroscopy of the hip for FAI under the care of a single surgeon. The minimum follow-up was one year (mean 3.2 years (1 to 7)). The responses to the modified Harris hip score were translated using the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 29 publications
2
59
4
1
Order By: Relevance
“…We found no difference between the two groups in terms of the change of mHHS at 6 months (PA = 12.8, RA = 11. [14,18,20]. Most studies of the sporting population have been retrospective in nature or in a small series of patients and do not report objective criteria to assess their level of activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no difference between the two groups in terms of the change of mHHS at 6 months (PA = 12.8, RA = 11. [14,18,20]. Most studies of the sporting population have been retrospective in nature or in a small series of patients and do not report objective criteria to assess their level of activity.…”
Section: Resultsmentioning
confidence: 99%
“…This work was performed in The Richard Villar Practice, Spire Cambridge Lea Hospital, Cambridge, UK. The Richard Villar Practice, Spire Cambridge Lea Hospital, 30 New Road, Impington, Cambridge CB24 9EL, UK e-mail: rvillar@uk-consultants.co.uk; rnv1000@aol.com 75% to 77% of patients at 1 year [14,18,20]. Botser et al [4] in a review comparing arthroscopy with open surgical dislocation and a combined approach for FAI found consistent improvement in modified Harris hip score (mHHS) for all with a lower complication rate and higher return to sports for professional athletes with the arthroscopic approach.…”
Section: Introductionmentioning
confidence: 99%
“…However, radiographic abnormalities suggestive of FAI have been demonstrated in asymptomatic patients and the natural history of the FAI hip is not completely known [3]. Significant hip-specific [4••], general health-specific [5], and quality-of-life [5] questionnaire improvements have been observed in early-and mid-term follow-up in symptomatic patients undergoing FAI hip preservation surgery. Nonetheless, it is unknown whether FAI and labral surgery has the potential to affect the incidence or progression of osteoarthritis of the hip [6].…”
Section: Introductionmentioning
confidence: 99%
“…Level III and IV studies of arthroscopic treatment of FAI report good to excellent results among outcome measures, including modified Harris Hip Score (HHS), Hip Outcome Score (HOS), visual analog pain score, hip morphology, patient satisfaction, quality of life, and return to activity [106][107][108][109][110][111][112][113][114]. A study by Bedi et al [115] confirmed that arthroscopic cam and/or rim osteoplasty result in significant improvement in hip kinematics and range of motion in symptomatic patients.…”
Section: Outcomes Limitations and Future Directionsmentioning
confidence: 98%